Efektivitas Kelas Ibu Hamil Terhadap Kesiapan Ibu Menghadapi Persalinan di Puskesmas Teluk Pucung - Helis Sukawati; Elfira Sri Futriani (Malahayati Nursing Journal, 2024)
ABSTRACT One of the interventions to reduce MMR, IMR and stunting that has been carried out is through education for pregnant women to improve their ability to monitor the health, nutrition of mothers and newborns. The class for pregnant women is a study group for pregnant women with a maximum number of participants of 10 people with a gestational age between 4 weeks to 36 weeks (before delivery). In this class pregnant women will learn together, discuss and exchange experiences about maternal and child health in a comprehensive and systematic manner and can be implemented on a scheduled and continuous basis. The purpose of attending this class is to prepare pregnant women physically and mentally. Knowing the effectiveness of pregnant women's classes on the readiness of mothers to face childbirth. Quasi-experimental with the type of research one group pre test-post test design. The sample for this study was all pregnant women who were registered at the Teluk Pucung Health Center in June 2023 as many as 36 people. The sampling technique used the paired simple t test. Before attending classes for pregnant women, most of the respondents were not ready for childbirth (69.4%), and those who were (30.6%) were ready. After attending the class for pregnant women, all respondents were ready to face childbirth (100%). Classes for pregnant women are effective for the readiness of mothers to face childbirth (p.value 0.000). Completeness of facilities and infrastructure to support class activities for pregnant women is improved. Keywords: Classes for Pregnant Women, Childbirth  ABSTRAK Salah satu intervensi penurunan AKI, AKB dan Stunting yang dilakukan adalah melalui edukasi ibu hamil untuk meningkatkan kemampuan pemantauan kesehatan, gizi ibu dan bayi baru lahir. Kelas ibu hamil adalah kelompok belajar ibu-ibu hamil dengan jumlah peserta maksimal 10 orang dengan usia kehamilan antara 4 minggu s/d 36 minggu (menjelang persalinan). Di kelas ini ibu-ibu hamil akan belajar bersama, diskusi dan tukar pengalaman tentang kesehatan ibu dan anak secara menyeluruh dan sistematis serta dapat dilaksanakan secara terjadwal dan berkesinambungan. Tujuan mengikuti kelas ini adalah mempersiapkan diri ibu hamil secara fisik dan mental. Tujuan Penelitian mengetahui efektivitas kelas ibu hamil terhadap kesiapan ibu menghadapi persalinan. Metode penelitian Quasi eksperimental dengan jenis penelitian one group pre test-post test design. Sampel penelitian ini adalah seluruh ibu hamil yang terdaftar di Puskesmas Teluk Pucung pada bulan Juni 2023 sebanyak 36 orang. Teknik pengambilan sampel menggunakan uji paired simple t test. Sebelum mengikuti kelas ibu hamil sebagian besar responden tidak siap menghadapi persalinan (69,4%), dan yang siap (30,6%). Sesudah mengikuti kelas ibu hamil semua responden siap dalam menghadapi persalinan (100%). Kelas ibu hamil efektif terhadap kesiapan ibu menghadapi persalinan (p.value  0,000). Kelengkapan sarana dan prasarana untuk menunjang kegiatan kelas ibu hamil ditingkatkan. Kata Kunci: Kelas Ibu Hamil, Persalinan